Neonatal Teeth and Riga-Fede Disease - Gerardo Rivera Silva; Hector R Martinez Menchaca (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
A 3 week-old male presented with ulceration on the ventral surface of the tongue. His parents informed that the patient had poor nutrients intake due to pain caused by tongue ulcer. The intraoral exploration showed ulceration of 10 mm diameter enclosed with a white fibrinous layer, situated on the ventral area of the tongue and two crows of neonatal teeth located in the mandibular anterior region (Figure 1). The incisal edges of teeth were smoothened about 2 mm. During a one-month follow-up his tongue ulcer disappeared.